Religious education and rituals during the COVID pandemic in the Islamic Republic of Iran (International relations and international law Journal, 2021)
This article is devoted to the study of religious education and religious rituals in Iran during the Covid-19 pandemic. The pandemic affected all aspects of human life, people were forced to move away from collective rituals and rituals, and education switched to an online format. One such area that has been subject to various disputes and debates due to the emergence of Covid-19 is religious education and religion in general. The cessation of community rituals, the closure of religious sites are the consequences of this virus. The article used a cognitive approach in the study of religion, religious rituals, religious education during the Covid-19 pandemic in Iran, and the authors also tried to determine how the external religious culture of eReligion was transformed during the pandemic, as well as how comfortable Iranian society feels in the conditions iReligion. Methods were used such as critical analysis, the principle of objectivity, a systematic approach to the study of the crisis, which forced the world order to develop according to a new scenario, a historical and analytical method of studying the state of religious education and religious institutions during a pandemic. In addition to these methods, the authors used an empirical research method that helped to increase the level of accuracy by conducting expert interviews in Persian on the Google Forms platform.Funding: The research in this article is carried out within the framework of the project “Religious institutions and practices in the context of digitalization and changes in social space during the COVID pandemic in Kazakhstan” funded by the Science Committee of the Ministry of Education and Science of the Republic of Kazakhstan (Grant No. AP08956706, 2020-2021), project leader Dr. L.Yerekesheva, Faculty of Oriental Studies, Al-Farabi Kazakh National University).Key words: religion, religious practices, religious education, world crisis, Covid-19 pandemic, Islamic Republic of Iran.